Schwann cell derived-peroxiredoxin protects motor neurons against hydrogen peroxide-induced cell death in mouse motor neuron cell line NSC-34 - Akiko Yamamuro-Tanabe; Yasuhiro Kosuge; Yuki Ishimaru; Yasuhiro Yoshioka (Journal of Pharmacological Sciences, 2023)
Schwann cells and oligodendrocytes secrete proteins that promote neuron survival, but their role in amyotrophic lateral sclerosis (ALS) is unclear. To address this question, we evaluated the effect of molecules secreted by Schwann cells on reactive oxygen species (ROS)-induced motor neuronal cell death. We observed that in motor neuron cell line NSC-34 cultures, the conditioned medium (CM) from Schwann cell line YST-1 (YST-1 CM) cultures had a protective effect against hydrogen peroxide-induced cell death. However, this protective effect of YST-1 CM was abolished by removing peroxiredoxin 1–4 (PRDX1–4) from the CM. We found that the expression of PRDX1 mRNA was markedly downregulated in the lumbar spinal cord of the superoxide dismutase 1 (SOD1)G93A mouse model of ALS. We also found that transient transfection of YST-1 cells with G93A SOD1 resulted in reduced PRDX1 mRNA expression. Additionally, in the mutant transfected cells, YST-1 CM showed decreased neuroprotective effect against hydrogen peroxide-induced NSC-34 cell death compared to those transfected with WT SOD1. Our results suggest that Schwann cells protect motor neurons from oxidative stress by secreting PRDX1 and that the reduction of PRDX secreted from Schwann cells contributes to increased ROS and associated motor neuronal death in ALS.